EFL teachers’ perceived language proficiency and teaching effectiveness - Yusuf, Fazri Nur; Novita, Ophelia Elisa (Indonesian Journal of Applied Linguistics, 2020)
The importance of language teachers possessing a high level of language proficiency has been extensively studied. On the other hand, studies related to teaching effectiveness (TE) have yet to define the concept of teaching effectiveness, and studies to relate teacher language proficiency (TLP) and TE, especially in the Indonesian context, are found to be scarce. In addition, the lack of both clear guidelines on how to assess TLP and current and official data of TLP in Indonesia only exacerbates this matter. Thus, the objective of this study was to find the relation between TLP and TE in the context of a language school in Bandung and the perception of its teachers on the role of TLP in the effectiveness of their teaching process. Using a mixed-methods sequential explanatory research design, the result of the data collection was then cross-tabulated and analyzed using the Fisher-Freeman-Halton exact test. It was found that there was a strong positive relation between TLP and the two aspects of TE: managing the classroom, and understanding and communicating lesson content, but no relation between language proficiency and assessing students and giving feedback. This was further confirmed in the qualitative stage that teachers with lower language proficiency could also deliver lesson content and assess students, albeit with a lower degree of flexibility compared to their more proficient counterparts. This means that the relation between TLP and TE was complex and not straightforward and that the mastery of one does not always entail the mastery of the other.